MASYARAKAT MADANI DALAM PERSPEKTIF AL- QUR'AN - Nurdinah Muhammad (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2017)
Civil society can not be separated from the history of Islamic civilization and also western civilization. From historical reviews it must be admitted that western societies are far more serious than Islamic societies, in increasing public domination of the state. When the western society has succeeded in abolishing the dominance of religion, monarchy and capital, the new Islamic society has escaped colonial domination. So it can not be denied that finally the nations of Islam should adopt many western thinking. The problem of civil society application in Islamic nations will surely be faced with the problem of government intervention which is badly needed on the unstable structure of society. Therefore, sometimes between civil society and government intervention often generate ambiguity for state officials. Therefore, alternative models of government intervention that will not dominate the society will be required, but on the contrary it will enable civil society to be characterized by the characteristics of, free public sphere, democracy, tolerance, pluralism and social justice.